First-principles calculation of adsorption of cadmium and lead on the surface of a 1T-MnO2 monolayer - Julieth V. Dita-Casiano; Mario L. Arteaga-Calderón; Gladys R. Casiano-Jiménez; César Ortega-Lopez; Miguel J. Espitia-Rico (PLoS ONE, 2025)
Manganese dioxide is a material with varied and interesting applications, especially including energy storage, the elimination of organic contaminants, and the removal of toxic atoms and molecules that pollute the environment. In this paper, the adsorption of toxic atoms of cadmium (Cd) and lead (Pb) on the surface of a 1T-MnO 2 monolayer is investigated using first-principles calculations. The calculated values of the adsorption energy show that the most energetically favorable site for the Cd and Pb atoms is P Mn . This occurs when a Cd or Pb atom is located just above a Mn atom, with adsorption energies of −0.883 eV and −5.918 eV, respectively. The charge transfer in the 1T-MnO 2 adsorbate/monolayer interaction is determined via the Bader charge. Additionally, the thermodynamic, mechanical, and dynamic stability of a pristine 1T-MnO 2 monolayer is determined through calculations of the formation energy, elastic constants, and dispersion curves of the phonon density of states and the band structure, respectively. Our study suggests that the 1T-MnO 2 monolayer is a good material for adsorption of the toxic heavy metal atoms of Cd and Pb.